Renal tuberculosis mimic Renal cell carcinoma - มโนรมณ์ ดนัย (Insight Urology, 2019)
The prevalence of renal tuberculosis in Thailand was high but few have been reported. We reported a case of 34-year old Thai female with large masses in right kidney ,liver and enlarge lymph node in abdominal cavity. Renal mass looked like end stage of carcinoma, but pathology report of renal tissue suspected tuberculosis. Treatment with TB drugs were administrated for 6 months .Monitor by CT scan of the abdominal cavity after 6months have been reported no disease was found.